Bioorthogonal Click Chemistry Enables Site‐specific Fluorescence Labeling of Functional NMDA Receptors for Super‐Resolution Imaging. Issue 50 (15th November 2018) - Neubert, Franziska; Beliu, Gerti; Terpitz, Ulrich; Werner, Christian; Geis, Christian; Sauer, Markus; Doose, Sören
Abstract: Super‐resolution microscopy requires small fluorescent labels. We report the application of genetic code expansion in combination with bioorthogonal click chemistry to label the NR1 domain of the NMDA receptor. We generated NR1 mutants incorporating an unnatural amino acid at various positions in order to attach small organic fluorophores such as Cy5‐tetrazine site‐specifically to the extracellular domain of the receptor. Mutants were optimized with regard to protein expression, labeling efficiency and receptor functionality as tested by fluorescence microscopy and whole‐cell patch clamp. The results show that bioorthogonal click chemistry in combination with small organic dyes is superior to available immunocytochemistry protocols for receptor labeling in live and fixed cells and enables single‐molecule sensitive super‐resolution microscopy experiments. Abstract : The extracellular part of the NR1 domain of the NMDA receptor was labelled by genetic code expansion in combination with bioorthogonal click chemistry. Receptor labeling with small organic dyes has advantages over immunocytochemistry protocols in live‐cell and super‐resolution imaging.